Soil respiration characteristics of different fertilization types in peach farms in Beijing suburb - WANG Yan-ping; GAO Ji-xi; FENG Chao-yang; DU Xiang-ge (浙江大学学报. 农业与生命科学版)
For exploring accurately the difference of various fertilization types in peach land of Beijing, soil carbon flux diurnal variation of three typical fertilization types in peach farm of Pinggu in Beijing were measured continuously in summer with LI-8100 automated soil CO2 flux system. The results show that the diurnal curves of soil respiration rate under different fertilization types had a simple peak value. The soil respiration rate, soil CO2 flux during a day, soil CO2 flux during a month and soil CO2 flux during the peach growing season of organic manure plot were the highest, those of half organic manure plus half fertilizer were the lowest. Soil CO2 flux of fertilizer plot, half organic manure plus half fertilizer and organic manure during the peach growing season were 448.51, 332.35, 570.34 g CO2·m-2, respectively. The relationships between soil respiration rate and environmental factors, soil factors were extremely prominent, as well as the relationship between soil respiration rate and soil organic carbon, microbial number, microbial biomass carbon and soil water content. The fertilization type of half organic manure plus half fertilizer would be helpful in reducing soil CO2 flux.